ASPECTS discrepancies between CT and MR imaging: analysis and implications for triage protocols in acute ischemic stroke. (17th February 2016) - Hui, Ferdinand K; Obuchowski, Nancy A; John, Seby; Toth, Gabor; Katzan, Irene; Wisco, Dolora; Cheng-Ching, Esteban; Uchino, Ken; Man, Shu-Mei; Hussain, Shazam
Abstract : Background: Optimal imaging triage for intervention for large vessel occlusions remains unclear. MR-based imaging provides ischemic core volumes at the cost of increased imaging time. CT Alberta Stroke Program Early CT Score (ASPECTS) estimates are faster, but may be less sensitive. Objective: To assesses the rate at which MRI changed management in comparison with CT imaging alone. Methods: Retrospective analysis of patients with acute ischemic stroke undergoing imaging triage for endovascular therapy was performed between 2008 and 2013. Univariate and multivariate analyses were performed. Multivariate logistic regression was used to evaluate the effect of time on disagreement in MRI and CT ASPECTS scores. Results: A total of 241 patients underwent both diffusion-weighted imaging (DWI) and CT. Six patients with DWI ASPECTS ≥6 and CT ASPECTS <6 were omitted, leaving 235 patients. For 47 patients, disagreement between the two modalities resulted in different treatment recommendations. The estimated probability of disagreement was 20.0% (95% CI 15.4% to 25.6%). In a multivariate logistic regression, CT ASPECTS >7 (p=0.004) and admission National Institutes of Health Stroke Scale (NIHSS) score <16 (p=0.008) were simultaneously significant predictors of agreement in ASPECTS. The time between modalities was a marginally significant predictor (p=0.080). Conclusions: The study suggests that patients with NIHSS scores at admission of <16 and patients with CT ASPECTS >7 have a higher likelihood of agreement between CT and DWI based on an ASPECTS cut-off value of 6. Additional MRI for triage in patients with NIHSS at admission of >16, and ASPECTS of 6 or 7 may be more likely to change management. Unsurprisingly, patients with low CT ASPECTS had good correlation with MRI ASPECTS.